Analisis Penggunaan Chatbot AI sebagai Strategi Coping dalam Mengatasi Stres Akademik pada Siswa SMAN 9 Samarinda - Malika Nuansa Wicaksana; Yasintha Sari Pratiwi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the use of AI Chatbot as a coping strategy in overcoming academic stress in students of SMAN 9 Samarinda. This study uses a qualitative method with a phenomenological approach and descriptive research type to understand in depth the students' experiences in using AI Chatbot as a coping strategy against academic stress in SMAN 9 Samarinda. The research subjects consisted of two students who used AI Chatbot, with secondary data in the form of interviews with close friends and documentation of screenshots of conversation history. Data collection was carried out through semi-structured interviews, voice recordings, and documentation, with the researcher as the main instrument. The study was conducted in June-July 2025. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and verification of conclusions. Data validity was tested through source triangulation. The results showed that the use of AI Chatbot in students includes emotion-focused coping and problem-focused coping. Driving factors include a closed attitude, low emotional self-efficacy, less supportive social experiences, high academic pressure, ease of access, and AI Chatbot features. The impacts of use include assistance with emotional regulation and academic support, but they also carry the risk of dependence and inaccurate information. This study confirms the psychological impact of AI chatbot use based on phenomenological analysis and triangulation of data sources. This study recommends the need for school policies to provide classroom guidance on the wise use of ChatGPT.